Living with polypharmacy: a narrative interview study with older Pakistanis in East London - Najia Sultan; Deborah Swinglehurst (BMC Geriatrics, 2023)
Abstract Background Polypharmacy is a growing and major public health issue. It can be burdensome and risky for patients and costly to healthcare systems. Older adults and those from ethnic minority backgrounds are disproportionately affected by polypharmacy. This study focuses on medication practices among Urdu-speaking Pakistani patients, a significant ethnic group in the UK. Most existing research on medication practices within South-Asian communities centres on adherence, leaving the social and moral dimensions of polypharmacy unpacked. Understanding how British Pakistani patients understand and manage polypharmacy in the context of their daily lives is crucial to avoiding harmful polypharmacy. Methods In-depth narrative interviews were conducted with 15 first-generation Pakistani patients using the Biographical Narrative Interview Method. Participants were recruited from GP practices in East London. All participants were prescribed ten or more regular medications (a pragmatic marker of ‘higher risk’ polypharmacy) and were aged over 50. Interviews were conducted with a bilingual researcher at home and were designed to elicit narratives of patients’ experiences of polypharmacy in the context of their biographies and daily lives. Results Polypharmacy is enacted through networks of interpersonal and socio-material relationships. The doctor-patient relationship and the family network held particular significance to study participants. In addition, participants described emotional bonds between themselves and their medicines, identifying them as ‘forces for good’—substances which allowed them to maintain their health through the intercession of God. Meanings attributed to medicines and enacted through these social, emotional, and spiritual relationships contributed to emerging and sustaining polypharmacy. Conclusions Patients make sense of and manage treatments in culturally specific ways. Developing an understanding of how medication practices in different communities are enacted is important for informing meaningful and effective conversations with patients about their medicines. Our findings contribute to enabling the integration of culturally sensitive approaches to prescribing.